METODOLOGI PENELITIAN PENDIDIKAN - Zaenal Arifin (LP2M STIT Al-Hikmah Way Kanan, 2020)
Abstract The leader in an organization has an important role in directing and influencing his subordinates. Without the people who organize and direct an organization, the organization can achieve its goals in accordance with its vision and mission. Therefore, a leader figure is needed to be able to manage and organize the organization to achieve its goals. This study aims to examine the importance of leadership in organizations with a literary approach. This type of research is research with a literature study approach which is done by finding theoretical references in accordance with the case obtained. The leader is a positive and confident person who has a high vision, mission and ethical values, with the ability to convey ideas and be able to encourage and relate well with others. Leadership will be the determining factor for success in an organization. This is because leadership becomes a focal point for significant changes in the organization, leadership becomes a personality that has an impact and leadership is an art in creating organizational compatibility and stability. Keywords: Organization, Leadership